2022
DOI: 10.26803/ijlter.21.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Quality Education Delivery in Selected Public Universities in Ghana: Students’ Perceptions

Abstract: The increased demand for higher education in recent years has thrown into question the issue of quality service. The purpose of this study was to investigate the factors that students perceive as the determinants of quality education service in selected public universities in Ghana. Using a convergent parallel mixed-methods design, data were collected from 606 final year education students for the 2020/2021 academic year while six students were interviewed. From both quantitative and qualitative data, the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The study's results revealed that the trend of higher education reform must be intensified by maintaining the quality and quantity of skilled human resources and clear competencies per the basics of Human Resources (Nallbani, 2013). In addition, one of the determinants of quality education in higher education is quality human resources (Owusu, 2022). GACC's improvement strategy on Criterion 5 focuses on two things, namely; 1) Allocating targeted college funds based on needs and monitoring student service satisfaction; 2) Improving the quality of ICT system availability.…”
Section: Discussionmentioning
confidence: 99%
“…The study's results revealed that the trend of higher education reform must be intensified by maintaining the quality and quantity of skilled human resources and clear competencies per the basics of Human Resources (Nallbani, 2013). In addition, one of the determinants of quality education in higher education is quality human resources (Owusu, 2022). GACC's improvement strategy on Criterion 5 focuses on two things, namely; 1) Allocating targeted college funds based on needs and monitoring student service satisfaction; 2) Improving the quality of ICT system availability.…”
Section: Discussionmentioning
confidence: 99%